The neglected barrier to medication use: a systematic review of difficulties associated with opening medication packaging. (23rd October 2022) - Angel, Maria; Bechard, Louise; Pua, Yong Hao; Thilarajah, Shamala; Newton, Courteney; Sorensen, Amelia; Clark, Ross
Abstract: Difficulty opening medication packaging can have serious consequences that can lead to patient harm via medication mismanagement or poor adherence. However, the quality of literature pertaining to these issues has yet to be collated and critiqued. This systematic review examined cross-sectional studies that objectively examined the ability of participants to open different medication packaging. Of the 8, 692 studies identified, 12 met the inclusion criteria, all of which were direct observational studies given that prior research has identified a mismatch between self-report and actual ability. Scoring via the Appraisal Tool for Cross Sectional Studies revealed that the methodological quality of included studies was typically low. Study samples mostly consisted of older adults. All studies reported a non-negligible proportion of participants unable to open packaging, with the most difficulty associated with child-resistant containers. Several studies examined associations; however, no factor was consistently found to be significantly associated with the ability to open packaging. Despite these studies spanning >40 years, the packaging types examined remained largely the same. This suggests that, despite decades of research demonstrating that packaging is problematic, there has been a stagnation in medication packaging development. Whether this is attributed to a paucity of high-quality research, and therefore a lack of strong evidence that change is needed, is unclear. Future research should strive for better methodological quality, with generalisable cohorts assessed via observation in their home. If the problems identified in prior research persist, this may provide the impetus for change that is overdue in the medication packaging industry.